PROMOTING ACTIVE AND INTERACTIVE LEARNING IN A HIGHER EDUCATION ONLINE CLASS - Atri Nadia Astarina; Riana Herlinda (English Journal Literacy Utama, 2022)
This study investigates the use of Nearpod in a Higher Education teaching and learning process which was conducted online due to the COVID-19 pandemic. It focuses on evaluating how Nearpod can promote active and interactive learning that has become one of the challenges in managing online classes with a large number of students. This qualitative descriptive study employed classroom observations, interviews, and questionnaires to collect the data. The participants involved in this study were 100 students from a university in Bandung. The research findings reveal some benefits that a cloud-based education platform, Nearpod, is likely to be effective to attract students‘ attention and promote their interaction and engagement. The students have a good perception towards the use of this tool as it provides various, fun, and meaningful activities. Furthermore, it allows them to get immediate feedback individually as proof of their comprehension of the materials. On the other hand, the aforementioned strengths might be constrained by the unstable internet connection and limited capacity of the selected Nearpod type. Based on the study, it is recommended to use the platform with different levels to see whether it will be as effective and engaging as at a higher level.